Histopathological observations of periapical repair in teeth with radiolucent areas submitted to two different methods of root canal treatment - Leonardo, M. R. [UNESP]; Almeida, W. A.; Silva, L. A. da; Utrilla, L. S. (Williams & Wilkins, 1995)
Dogs' teeth with induced chronic periapical periodontitis were treated endodontically by two different methods, and the results were compared. A total of 40 root canals from the upper and lower premolars of two dogs were prepared chemomechanically. In method 1, a high-concentration (5.25%) hypochlorite solution was used during the instrumentation of the root canal, and an antibacterial dressing was applied between sessions, followed by filling of the root canal. In method 2, a low-concentration (0.5%) sodium hypochlorite solution was used as an adjunct to mechanical debridement, and the root canal was filled during the same session. The histopathological results showed that method 1 led to better periapical repair than method 2.